Pemberdayaan Perawat dalam Penerapan Nurse Early Warning System untuk Memantau Kondisi Pasien di Rumah Sakit - Junaedi Yunding; Masyita Haerianti; Evidamayanti Evidamayanti; Evawaty Evawaty; Indrawati Indrawati (Jurnal Abdimas Kesehatan (JAK), 2020)
AbstractSevere adverse events such as cardiac arrest and death are often marked by abnormal vital signs a few hours before the event. Majene Regional General Hospital is the only hospital in the Majene Regency and is a reference center for all puskesmas in the Majene and surrounding districts. As a health service institution that organizes health services, it is closely related to the responsibility of providing emergency services. The Nurse Early Warning System (NEWS) is a development in emergency services for patients treated in hospitals, which serves as an early detection tool so that if there is a decrease in the patient's condition it can be known earlier can be handled more quickly. The purpose of this activity is to increase the knowledge and skills of nurses in the application of the nurse early warning system (NEWS) in monitoring the condition of patients in the care room. The implementation method starts from identifying the problem, delivering material about NEWS, demonstrating the assessment of the patient's condition and the nurse's independent practice in using NEWS. The evaluation results of this activity are the increase in knowledge and skills of nurses using NEWS in monitoring the condition of patients in the care room.